Answer:
(-1/2,-5/2)
Step-by-step explanation:
x-y = 2
x+y = -3
---------------
Through Elimination, we can just add the system of equations. The y cancels out and gives us the single equation for x:
2x = -1
x = -1/2
Substitute -1/2 for x in either equation and you get:
(-1/2) + y = -3 Solve for y
y = -5/2
--------------
Consider functions f and g such that composite g of is defined and is one-one. Are f and g both necessarily one-one. Let f : A → B and g : B → C be two functions such that g o f : A ∴ C is defined. We are given that g of : A → C is one-one.
Its B, The answer for your question is B
Answer:
(- 4, 1 )
Step-by-step explanation:
Given the 2 equations
y = x + 5 → (1)
x - 5y = - 9 → (2)
Substitute y = x + 5 into (2)
x - 5(x + 5) = - 9 ← distribute and simplify left side
x - 5x - 25 = - 9
- 4x - 25 = - 9 ( add 25 to both sides )
- 4x = 16 ( divide both sides by - 4 )
x = - 4
Substitute x = - 4 into either of the 2 equations and evaluate for y
Substituting into (1)
y = - 4 + 5 = 1
Solution is (- 4, 1 )
Step-by-step explanation:
∆TSU=∆RSU (SAS).
HENCE,
NONe of the above statement is true.